2017
DOI: 10.3892/ol.2017.6114
|View full text |Cite
|
Sign up to set email alerts
|

Consecutive stimulation of HBsAg promotes the viability of the human B lymphoblastoid cell line IM-9 through regulating the SIRT1-NF-κB pathway

Abstract: Abstract.Patients with chronic HBV infection have been reported to suffer a significantly increased risk of NHL, but the underlying mechanisms remain to be clearly explained. The aim of the present study was to clarify the relationship between chronic HBV infection and NHL development. Fluorescence-activated cell sorting, Annexin V/7-aminoactinomycin D staining and MTS assay were used to analyze the rate of apoptosis and cell viability. In addition, western blotting was used to detect protein expression. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…The possible mechanism of these cells development may be that chronic antigenic stimulation might cause sustained activation and proliferation of B-cells, predisposing to DNA damage, cytogenetic aberrations, overexpression of proto-oncogenes and transformation into SIBC. JIAN BO and coworkers demonstrated that HBsAg was able to promote cell viability and to reduce apoptosis in the human peripheral lymphoblastoid cell line, IM-9 through the SIRT1‑NF‑κB signaling pathway [38]. Another research found that CDR3 sequences of Ig exhibited a significant homology to HBsAb in HBsAg positive DLBCL, suggesting that HBV-associated DLBCL might originate from HBV antigen-selected B cells [39].…”
Section: Discussionmentioning
confidence: 99%
“…The possible mechanism of these cells development may be that chronic antigenic stimulation might cause sustained activation and proliferation of B-cells, predisposing to DNA damage, cytogenetic aberrations, overexpression of proto-oncogenes and transformation into SIBC. JIAN BO and coworkers demonstrated that HBsAg was able to promote cell viability and to reduce apoptosis in the human peripheral lymphoblastoid cell line, IM-9 through the SIRT1‑NF‑κB signaling pathway [38]. Another research found that CDR3 sequences of Ig exhibited a significant homology to HBsAb in HBsAg positive DLBCL, suggesting that HBV-associated DLBCL might originate from HBV antigen-selected B cells [39].…”
Section: Discussionmentioning
confidence: 99%
“…HBV is hepatotrophic and lymphotrophic. Bo et al [12] co-cultured HBsAg with the human lymphoblastoid cell line IM-9 in vitro and found that chronic HBsAg stimulation could promote the viability of IM-9 cells by regulating the sirtuin 1(SIRT1)-nuclear factor-κB(NF-κB) pathway, finally resulting in the formation of HBV-associated NHL. In a clinical study involving 313 Chinese patients with NHL [13], the HBsAg positivity rate was 12.7%, which was higher than that of the general population (7.2%).…”
Section: Hbvmentioning
confidence: 99%
“…Hepatitis B virus (HBV), a hepatotropic virus, can also infect peripheral blood mononuclear cells and lymph nodes [1]. HBV infection has been found to play a causative role in lymphomagenesis by either chronic antigenic simulation model [2] or antigen-independent mechanism [3]. An epidemiological study involving 603,585 participants showed that hepatitis B surface antigen (HBsAg)-positive participants had an increased risk of non-Hodgkin lymphoma (NHL) overall compared with those who were HBsAg-negative (hazard ratio = 1.74).…”
mentioning
confidence: 99%